Respon imun nonspesifik dan pertumbuhan udang vaname (Litopenaeus vannamei) yang diberi pakan yang ditambahkan nukleotida dengan lama pemberian berbeda - Manoppo, Henky (Universitas Sam Ratulangi, 2014)
Abstract This study evaluated the effects of feeding protocol of nucleotide-supplemented diet on total hemocytes, PO activity and growth of whiteleg shrimp. Shrimp juveniles were reared in five 120-l glass aquaria at the density of 25 juveniles each. Shrimp pellet was supplemented with nucleotides mixture at 400 mg.kg-1 diet. Shrimps were fed three time a day at 3%/bw/d. Feeding protocol was 7 days nucleotides diet – 7 days basal diet alterably for 49 days. Total hemocyte count, PO activity, and growth were measured at the end of experiment. Research result showed that oral administration of nucleotides at seven days interval did not affect THC, PO activity, and growth of shrimp. But if the feed was administered successively for four weeks, supplementation of nucleotides would significantly enhance the nonspecific immune response and shrimp growth. Keywords: Litopenaeus vannamei, nucleotides, PO activity, total hemocyte count